Digital Payments, QRIS Growth, and State-Owned Bank Portfolio Returns in Indonesia - Bisri, Bisri; Siwi, Herlin Wida (Yayasan Pendidikan Penelitian Dan Pengabdian Al-amsi, 2025)
This study examines whether QRIS growth and digital payment activity are associated with the equal-weight stock-return portfolio of Indonesian state-owned banks. Using a balanced exact-month sample of 12 observations drawn from official Bank Indonesia publications and market data, the article places correlation analysis at the center of the empirical design and treats parsimonious OLS-HC3 regressions as supporting evidence only. The results show that QRIS growth has a near-zero association with portfolio returns, while logged digital payment activity displays only a weak and unstable relationship once simple macro controls are introduced. These findings suggest that aggregate payment-system expansion should not be interpreted as an immediate stand-alone signal for short-run stock returns in state-owned banks. The article contributes by offering a cautious measurement-first design for Indonesian digital-finance research and by showing that policy-relevant payment-system deepening does not necessarily translate into contemporaneous market revaluation within a small balanced monthly window.